2020
DOI: 10.1159/000508237
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in a Case of Refractory Idiopathic Orbital Inflammation: 6-Year Follow-Up Outcomes

Abstract: Idiopathic orbital inflammation (IOI) is a noninfectious inflammatory disease whose etiology remains unknown. Treatment is focused on reducing inflammation, which becomes challenging in nonresponding cases. We report the case of a 59-year-old woman with refractory IOI that showed a positive response to tocilizumab therapy. The patient was diagnosed with a unilateral sclerosing IOI for 9 years and showed a negative control with previous oral steroids, peribulbar steroid injections, radiotherapy, immunosuppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…Most studies are case reports or case series. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Only one randomized clinical trial has been published, 44 and the remaining reports include a prospective interventional nonrandomized study, 45 2 observational 46,47 an open-label multicenter, 48 and a retrospective longitudinal study. 49 Table 2 shows the 2 comparative studies found.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies are case reports or case series. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Only one randomized clinical trial has been published, 44 and the remaining reports include a prospective interventional nonrandomized study, 45 2 observational 46,47 an open-label multicenter, 48 and a retrospective longitudinal study. 49 Table 2 shows the 2 comparative studies found.…”
Section: Resultsmentioning
confidence: 99%
“…Andere Gruppen berichten über Erfolge mit Azathioprin, Mycophenolat-Mofetil (MMF), Tocilizumab, Rituximab, Infliximab und Adalimumab [266][267][268][269][270][271][272]. Leider ist die Datenlage zu dem Einsatz dieser Medikamenten bei IOI begrenzt und es fehlen prospektive Studien.…”
Section: Biopsieunclassified
“…Smith und Rosenbaum behandelten 57 % der IOI-Patienten erfolgreich mit Methotrexat (15–25 mg pro Woche) 265 . Andere Gruppen berichten über Erfolge mit Azathioprin, Mycophenolat-Mofetil (MMF), Tocilizumab, Rituximab, Infliximab und Ada-limumab 266 267 268 269 270 271 272 . Leider ist die Datenlage zu dem Einsatz dieser Medikamenten bei IOI begrenzt und es fehlen prospektive Studien.…”
Section: Orbitale Autoimmunerkrankungenunclassified
“…Tocilizumab is a humanized monoclonal IgG1 antibody that inhibits the molecular actions of IL-6 by binding to its receptor (i.e., IL6R)-either the soluble or membrane-bound receptor [176,177]. Tocilizumab was shown to prevent the recurrence of NSOI in a 59-year-old patient with refractory NSOI over a span of 6 years when used at a maintenance dose of 4 mg/kg and following an initial treatment at a dose of 8 mg/kg [178]. However, in another case report, it was demonstrated that an initiation dose of 4 mg followed by 8 mg every 4 weeks to treat orbital pseudotumor couldn't achieve inflammation control at 9 months [179].…”
Section: Interleukin-6 Receptor Binding Agentsmentioning
confidence: 99%